Health Status Of Sacrificial Animals In Kupang City In 2020 Based On Anthemortem And Postmortem Examination - Novie Hellen Manongga; Herlina U Deta; Aji Winarso (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Slaughter of sacrificial animals is generally done in mosques on the day of sacrifice or Eid al-Adha. Animals that are commonly used as sacrifices such as camels, cows, buffaloes, goats, and sheep. Before slaughtering sacrificial animals, it is very important to conduct antemortem and postmortem examinations. This library study was conducted from November to December 2020 which includes the collection of data on the 2020 sacrificial assistance report from the Kupang City Agriculture Office and offline and online reference/library searches. Sacrificial animal data obtained from the Kupang City Agriculture Office and reference/library sources obtained are analyzed descriptively and discussed based on the results of research from various sources. The results of the library study showed that the total sacrificial animals in 2020 as many as 2,645 consisting of 1,537 cows, 1,107 goats, and 1 sheeps. An antemortem and postmortem examination showed normal results. The sacrificial animal was examined by 86 veterinarians and 160 paramedics.